Black & white relations: Intimate relationships of patients with borderline personality disorder - Ociskova, Marie; Prasko, Jan; Hodny, Frantisek; Holubova, Michaela; Vanek, Jakub; Minarikova, Kamila; Nesnidal, Vlastimil; Sollar, Tomas; Slepecky, Milos; Kantor, Krystof (Neuro-endocrinology letters, 2023)
BACKGROUND: Individuals with borderline personality disorder (BPD) suffer from an excessive fear of abandonment, leading to tense moments in their intimate relationships. These struggles translate into lower marital satisfaction perceived by both intimate partners. However, this connection is bidirectional, since conflicts with a romantic partner are the most common precipitating factors of decompensation in BPD patients. METHOD: This narrative review was performed using PubMed, Web of Science, and Scopus databases with keywords "borderline personality disorder", "partnership", marital problems", and "marital conflicts". Articles, books, and book chapters published within January 1980 - December 2020 were extracted and analysed. Additional sources were found while reviewing references of relevant articles. The total of 131 papers met the inclusion criteria. RESULTS: Patients with BPD struggle with reaching marital satisfaction. They often find themselves in disharmonic and unfulfilling relationships. The association between the relationship issues and BPD may partly come from misunderstanding one or both partners' behaviour. Individuals with BPD tend to misinterpret their partner's behaviour, struggle with communication, and sometimes be verbally and physically aggressive. They often do not recognize that their intrapersonal processes influence their interpersonal struggles. Understanding the role of the maladaptive personality traits in the relationship and their management could be beneficial for both partners. CONCLUSION: Individuals with BPD often report dysfunctional romantic relationships characterized by insecure attachment, maladaptive communication, and lower relationship satisfaction. Future studies should focus on finding effective strategies of couples ́ therapy working with this population.
Keywords: interpersonální vztahy; manželství; lidé; sexuální chování; hraniční porucha osobnosti; Sexual Behavior; Family Conflict; Borderline Personality Disorder; Humans; Marriage; konflikt v rodině; Interpersonal Relations